THE POTENTIAL OF TITHONIA DIVERSIFOLIA (WILD SUNFLOWER) AS ORGANIC FOLIAR FERTILIZER - Dela Pena, Cenny; I. Bartolome, Leah. D.; Banwa, Tules.P. (European Scientific Journal, ESJ, 2014)
Indigenous farming practices include the use of wild plants like sunflowers to sustain crop production. This practice becomes the present trend in sustainable agriculture aside from promoting healthful living, safe environment and improving economic condition. This study was conducted to determine the potential of Thitonia diversifolia (wild sunflower) as organic foliar fertilizer using pechay (Brassica rapa L.) as experimental plant. The randomized complete block design was used with the mixture ratio of water with sunflower leaves and stems as treatments with three replications including positive and negative treatments. The different treatments were applied to a pechay plant. The weight and height of the pechay plant were measured after application. The treatment weight and height means were compared using the analysis of variance. Significant means were further compared using the least significant difference. The gathered data were analyzed using the SPSS version 12. Results showed that of the experimental treatments, the mixture ratio of 1.5kg sunflower leaves to 1L water had the highest pechay plant weight and height means which do not significantly differ to that of the positive control treatment. This shows a comparable potential of Thitonia diversifolia (wild sunflower) as foliar fertilizer that can be tested in other crops.